Psycholinguistic Mechanisms of the Formation of Coherent Speech in Typically Developing and Intellectually Disabled Children - Saipova , Xilola (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
Tthere are qualitatively significant differences between the psycholinguistic mechanisms of coherent speech formation in healthy and mentally retarded primary school students. These differences are manifested at all stages of the speech formation process - motivational, programming, lexico-grammatical, and motor.